Transformasi Spasial Fisik dan Teritorial Pada Bangunan Cagar Budaya. Studi Kasus: Museum Gedung Sate, Bandung - Vika Haristianti; Aida Andrianawati; Idhar Resmadi (RUAS, 2022)
This study aims to discuss the extent to which the spatial transformation due to the renovation of cultural heritage buildings can affect the physical building and the user's territory, as well as its influence on the concept of architecture as the language of development. This study uses a qualitative method. Data was collected by field observations, interviews, and literature review. The sampling was carried out using a non-random or purposive type of sample. The results of the analysis show that there has been a physical and territorial transformation in Gedung Sate, Bandung as an effect of the construction of the Gedung Sate Museum. The control role of stakeholders also greatly influences the extent to which this transformation takes place. Not only interior elements, space layouts, as well as facade elements, and user territories have changed. Furthermore, the existing transformation more or less also affects development in the Gedung Sate area, and for the city of Bandung in general. Where the role of Gedung Sate's architecture is now becoming broader and more abstract. Not only becomes an artifact, but also becomes something more economic and commercial (commodification).